47 A Survey of Microbiology Consultations in an Urban Academic Center. (11th January 2018) - McMullen, Phillip; Chan, Ernest; Tesic, Vera; Beavis, Kathleen; Charnot-Katsikas, Angella
Abstract: Many clinical decisions are made daily based on the laboratory results generated within the clinical microbiology laboratory. Despite advances in laboratory methods that have increased automation and simplicity in generating laboratory results, consultation and review of the results with a microbiologist is still often necessary prior to reporting the final outcome of testing. To determine the most common reasons for and outcomes of consultation, we surveyed attending microbiologists and pathology residents covering the microbiology service at an urban academic center. Respondents were asked to supply information concerning the question raised by microbiology or clinical staff, the response by the clinical microbiology attending, and the ultimate resolution of the issue. A total of 29 complete consultations was reported over a 10-day period in February 2017. The nature of the consults was as follows: 15 (51.7%) concerned guidance related to the identification or susceptibility testing of clinical isolates, seven (24.1%) involved recommendations for additional testing (including send-out testing), six (20.7%) involved direct recommendations regarding antimicrobial therapy, and one (3.5%) involved enhanced monitoring and hospital infection control. Eighteen (62.1%) of the consults were initiated by microbiology technologists directly or during microbiology rounds, and nine (31.0%) were initiated by the clinicians caring for the patients. Two (6.9%) consults came from infection control. The consults ranged across a variety of laboratory sections, with the majority coming from bacteriology and virology. Twenty-two (75.9%) consults involved bacterial cultures and six (20.7%) pertained to viral testing. Within bacteriology, four consults (18.2% of the total bacteriology consults) were regarding test results indicating organisms with multidrug resistance. In virology, three of the consults (50% of the total virology consults) were specifically concerning HIV testing interpretation and guidance on follow-up testing. The direct clinical outcomes of the consults were broken down into four broad categories: directing antimicrobial therapy (n = 11, 37.9% of total consults), performing additional testing and microbiological workup (n = 8, 27.6%), removing infected devices (n = 2, 6.9%), and implementing infection control practices (n = 1, 3.5%). There were seven consults (24.1%) with an unknown or unclear direct clinical outcome. Overall, 22 of the 29 consults, or 75.9%, directly influenced patient care and management. In summary, most of the consults surveyed in this study were regarding bacterial culture results, and most consults occurred between laboratory technologists and the microbiologist on duty. It was also common for the microbiologist to consult directly with the clinical team (31.0% of consults). Limitations of this study include the short time frame as well as a likely underestimation of consults performed. Nonetheless, this study highlights the diversity of microbiology consultations performed by attending pathologists and the frequency with which these lead to impactful clinical decisions that directly influence the management of patients.